خصائص الخطاب المسردي في مسردية غنائية الحب والدم لعز الدين جلاوجي - بوخزنة لبنة; رحومة هاجر; بوسكاية شهلة; غضبان تركية (جامعة الوادي - University of Eloued, 2025)
The works of Ezzedine Jalouji are distinguished by their uniqueness and the emergence of innovation in them, especially what he called narrative. They have been considered a fertile field for analyzing the narrative structure and exploring the mechanisms of forming meaning within the text, as Jalouji does not present the narrative as a mere means of conveying the story, but rather gives it an artistic and aesthetic function. In which language, structure and meaning are intertwined, we find it in the narrative of “The Lyric of Love and Blood,” whose events take place in ancient times, where its hero, Amer, sought to combine his love, for which he traveled countries and deserts to reach, with his sense of responsibility and love for his homeland. What makes the story enter into conflicts represented by wars, betrayal and treachery from the enemy and the family, and the narrative depicts for us how greed for power may result in wars, as Munad covets the leadership that Amer was assuming and seeks to kill him, then after his attempt failed, he sought to spoil his request to marry the prince’s sister, Aljiya, by spreading discord between them, The narrative depicts that whoever follows the truth will be saved in this world, and depicts the values ​​of loving one's homeland and dying for it.
مذكرة .ليسانس . اللغة والأدب العربي . 2025.